Ultrarapid Endoscopic-Aided Hematoma Evacuation in Patients with Thalamic Hemorrhage - Kuan-Yu Chen; Woon-Man Kung; Lu-Ting Kuo; Abel Po-Hao Huang (Behavioural Neurology)
Thalamic hemorrhage bears the worst outcome among supratentorial intracerebral hemorrhage (ICH). Minimally invasive endoscopic-aided surgery (MIS) has been proved to be safe and effective in evacuating ICH. However, the ideal timing of MIS is still a controversy. In this study, we present our experience in the treatment of patients with thalamic hemorrhage by ultrarapid MIS evacuation. This retrospective analysis enrolled seven patients treated with ultrarapid MIS evacuation of thalamic hemorrhage. Seven patients treated with EVD with similar ICH score were included as match control. Primary endpoints included rebleeding, morbidity, and mortality. Hematoma evacuation rate was evaluated by comparing the pre- and postoperative computed tomography (CT) scans. Glasgow Outcome Scale Extended (GOSE) and modified Rankin Score (mRS) were noted at the 6-month and 1-year postoperative follow-up. Among the seven patients, six were accompanied with intraventricular hemorrhage. All patients received surgery within 6 hours after the onset of stroke. The mean hematoma volume was 35 mL, and the mean operative time was 116.4 minutes. The median hematoma evacuation rate was 74.9%. There was no rebleeding or death reported after the surgery. The median GOSE and mRS were 3 and 5, respectively, at 6 months postoperatively. Further, 1-year postoperative median GOSE and mRS were 3 and 5, respectively. The data suggest that the ultrarapid MIS technique is a safe and effective way in the management of selected cases with thalamic hemorrhage, with favorable long-term functional outcomes. However, a large, prospective, randomized-controlled trial is needed to confirm these findings.